Analisis Struktur dan Strategi Nafkah Rumah Tangga Nelayan di Desa Sangrawayang, Sukabumi - Mariska Putri Nur Hidayah; Dadang Shafrudin; Eddy Supriyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
This research was conducted in Sangrawayang Village, Sukabumi Regency, West Java. This study aims to analyze the livelihood structure and strategies of fishermen household in Sangrawayang Village, Simpenan District, Sukabumi Regency. This study uses a qualitative approach through in-depth interviews, literature studies and the results of writing field notes during field breaks. The method used in this study is a qualitative approach as a research procedure that produces descriptive data. The results showed that the fisherman households in Sangrawayang Village were classified into three classifications of structures or sources of income that were modified into the sectors of on fishing economy, off-fishing economy and non-fishing economy. The livelihood strategies of fishermen households in Sangrawayang Village are classified as double, namely the livelihood of fishermen and also as a processor for catching salted fish and farm laborers. Keywords: Livelihood strategies, Livelihoods structure.